The Luminosity Phase Space of Galactic and Extragalactic X-Ray Transients Out to Intermediate Redshifts - Polzin, Ava; Margutti, Raffaella; Coppejans, Deanne L.; Auchettl, Katie; Page, Kim L.; Vasilopoulos, Georgios; Bright, Joe S.; Esposito, Paolo; Williams, Peter K. G.; Mukai, Koji; Berger, Edo (IOP, 2023)
We present a detailed compilation and analysis of the X-ray phase space of low- to intermediate-redshift (0 ≤ z ≤ 1) transients that consolidates observed light curves (and theory where necessary) for a large variety of classes of transient/variable phenomena in the 0.3-10 keV energy band. We include gamma-ray burst afterglows, supernovae, supernova shock breakouts and shocks interacting with the environment, tidal disruption events and active galactic nuclei, fast blue optical transients, cataclysmic variables, magnetar flares/outbursts and fast radio bursts, cool stellar flares, X-ray binary outbursts, and ultraluminous X-ray sources. Our overarching goal is to offer a comprehensive resource for the examination of these ephemeral events, extending the X-ray duration-luminosity phase space (DLPS) to show luminosity evolution. We use existing observations (both targeted and serendipitous) to characterize the behavior of various transient/variable populations. Contextualizing transient signals in the larger DLPS serves two primary purposes: to identify areas of interest (i.e., regions in the parameter space where one would expect detections, but in which observations have historically been lacking), and to provide initial qualitative guidance in classifying newly discovered transient signals. We find that while the most luminous (largely extragalactic) and least luminous (largely Galactic) part of the phase space is well populated at t > 0.1 days, intermediate-luminosity phenomena (L X = 1034-1042 erg s-1) represent a gap in the phase space. We thus identify L X = 1034-1042 erg s-1 and t = 10-4 to 0.1 days as a key discovery phase space in transient X-ray astronomy.
Keywords: 1810; 1825; 1851; 1852; 2109; 739; Astrophysics - High Energy Astrophysical Phenomena; High energy astrophysics; Time domain astronomy; Transient sources; X-ray astronomy; X-ray telescopes; X-ray transient sources